USING FACEBOOK-BASED SOCIAL MEDIA IN SUPPORTING MARKETING EQUIPMENT ACTIVITIES TRADITIONAL AGRICULTURE - Yunus Winoto; Kaizeno Globi Cancerine; Rully Kairul Anwar (Metakom, 2019)
The method used uses a qualitative approach to the type of action research research. There are five stages in the research that begin the diagnosis stage, the planning, implementation, evaluation and learning stages. At the stage of the action in the form of creating a Facebook page for Galonggong craftsman marketing activities with the name '' Galonggong Tasik Village Crafts '' and the user name is @ kerajinangalonggong.tas1k. As for the results of an evaluation of the design of Facebook-based social media development in supporting the marketing activities of agricultural equipment craftsmen in the village of Galonggong Tasikmalaya in the form of a Facebook page with the name "Handicraft Kampong Galonggong Tasik" that this page has been assessed and received very well by the craftsmen and said to have been suitable for use in the marketing of products from the agricultural tools of the village of Galonggong Tasikmalaya.